Cross-dialectal Arabic translation: comparative analysis on large language models - Beidas, Ayah; Mohi, Kousar; Ghaddar, Fatme; Ahmad, Imtiaz; Abed, Sa'Ed (Frontiers in Artificial Intelligence, 2025)
IntroductionExploring Arabic dialects in Natural Language Processing (NLP) is essential to understand linguistic variation and meet regional communication demands. Recent advances in Large Language Models (LLMs) have opened up new vistas for multilingual communication and text generation.MethodsThis paper investigates the performance of GPT-3.5, GPT-4, and Bard (Gemini) on the QADI and MADAR datasets, while GPT-5 was evaluated exclusively on MADAR encompassing over 15 different countries. Several metrics have been used in the evaluation, such as cosine similarity, universal similarity encoder, sentence BERT, TER, ROUGE, and BLEU. In this study, different prompting techniques were used: zero-shot and few-shot. Zero-shot was employed for all dialects, and few-shot was employed only for the least translation performance dialect, Tunisian.ResultsAnalysis revealed that in the QADI dataset, GPT-4 significantly outperformed others in translating MSA to DA, with ANOVA tests showing strong significance (p < 0.05) in most metrics, except for BLEU and TER where it does not show significance, indicating comparable translation performance among models. Furthermore, GPT-4 was highest in semantic similarity compared to GPT-3.5 and Bard (Gemini), 0.66, 0.61, and 0.63, respectively. GPT-4 was the best in identifying overlapping sentences (i.e., those where the source and target are identical) with a combined average of 0.41 in BLEU and ROUGE-L. All LLMs scored TER values between 6% and 25%, indicating generally good translation quality. However, GPT models, especially GPT-5, responded better to prompting and translation to Levant countries compared to Bard (Gemini). For the MADAR dataset, no significant translation differences were observed in sentence-BERT, ROUGE-L, and TER, while differences are identified in cosine similarity, BLEU, and universal similarity encoder metrics. Therefore, GPT-5 is the top performer in identifying sentence overlaps measured by BLEU and ROUGE-L (combined average 0.37).DiscussionThe few-shot approach did not show a significant improvement in translation performance, especially for GPT-4 and Bard (Gemini), while GPT-3.5 performed consistently. Zero-shot prompts were effective across dialects, while few-shot prompting, applied to the weakest-performing dialect (Tunisian), did not yield improvement. GPT-4 and Bard performed worse under this set-up, while GPT-3.5 remained consistent.